ANGKA KETAHANAN HIDUP 3 TAHUN PASIEN KARSINOMA NASOFARINGS YANG MENDAPAT NONCONCURRENT CHEMOTHERAPY DI BAGIAN TELINGA HIDUNG TENGGOROK â KEPALA LEHER RSUP DR. SARDJITO PADA TAHUN 2008-2010 - , RYAN FERALDY HAROEN; , dr. Sagung Rai Indrasari, M.Kes., Sp.THT-KL(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Nasopharyngeal carcinoma (NPC) is one of those cancers whose incidence and mortality rate are still high in Indonesia. The standard therapy for NPC is a chemotherapy that is given concurrently with radiotherapy (concurrent chemoradiotherapy). However, not all patients receive concurrent chemoradiotherapy because of other factors such as its availability and patient's type of insurance. These patients will undergo a different type of therapy, an adjuvant chemotherapy or a neoadjuvant chemotherapy or other, which are not the standard therapy. Objective: To determine the 3-years survival rate of patients with NPC that acquired any therapy other than CCRT in RSUP Dr. Sardjito, Yogyakarta. Method: A descriptive-analytical study using Kaplan-Meier survival analysis to the 3-years survival of NPC patients who did not undergo CCRT. Samples are obtained from January 2008 to December 2010, where 64 NPC patients met the inclusion and exclusion criteria. Result: The 3-years survival rate of NPC patients who acquired any other therapy than CCRT is 32,8% with a mean survival of 21 months altogether.